(untitled) (Bangladesh Journal of Animal Science, 2014)
Six hundred day-old unsexed broiler chicks were used in a 42-day trial to compare the effects of different levels of palm oil supplementation on feed intake, weight gain, feed conversion and carcass quality of broilers. The chicks were randomly distributed following a completely randomized design in four treatment groups having three replications per treatment. Each treatment had 150 broilers with 50 broilers per replicate. Four diets were formulated using locally available ingredients as diet without oil, diets containing 2.5%, 3.0% and 3.5% palm oil. All broilers had free access to ad libitum feeding. Results indicated that, supplementation of diets with different levels of palm oil significantly (p<0.05) influenced feed intake of broiler only at the age of 6th week. It was observed that as the level of supplementation increased, feed intake gradually decreased up to 6th week. Supplementation of diets with different levels of palm oil increased live weight gain of broilers. Differences (p<0.01) were observed at the end of 4th, 5th and 6th weeks of age only. Use of different levels of palm oil significantly (p<0.05) changed blood weight, heart weight and dressed weight. Survivability of broilers was higher in the supplemented group compared with without oil group. It was concluded that, supplementation of palm oil at 3.5% level in the diet of broilers resulted higher weight gain, better feed conversion and improved carcass characteristics comparing other levels. It may be concluded that supplementation of palm oil at 3.5% level in the diet of broilers resulted significantly (p>0.05) higher feed conversion ratio compared to 2.5% and 3.0% levels. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19384 Bang. J. Anim. Sci. 2014. 43 (1): 45-51